Pengukuran Tingkat Maturity Tata Kelola Sistem Informasi Rumah Sakit dengan Menggunakan Framework Cobit Versi 4.1 - Ricky Rohmanto Rohmanto; Miki Wijana Wijana; Sarah Nurfadhilah Nurfadhilah; Mohammad Erdda Habiby Habiby (Masoem University, 2025)
The utilization of information technology (IT) in hospitals plays a strategic role in improving healthcare service quality, operational efficiency, and managerial decision-making. Along with the increasing dependence on information systems, effective IT governance is required to ensure alignment with organizational objectives and proper risk management. This study aims to measure the maturity level of information system governance at dr. Slamet General Hospital, Garut, using the COBIT 4.1 framework. This research employs a descriptive quantitative approach. Data were collected through observations, interviews, documentation studies, and questionnaires developed based on the COBIT 4.1 domains and processes, namely Plan and Organise (PO), Acquire and Implement (AI), Deliver and Support (DS), and Monitor and Evaluate (ME). The results indicate that the overall maturity level of information system governance at dr. Slamet General Hospital is 2.59, which corresponds to Level 2 (Repeatable but Intuitive). The Deliver and Support (DS) domain achieved the highest maturity level, while the Monitor and Evaluate (ME) domain showed the lowest level. These findings reveal a gap between the current condition of IT governance and the expected maturity level. Therefore, continuous improvement in information system governance is necessary through the establishment of formal policies, process standardization, and the implementation of regular monitoring and evaluation mechanisms to effectively support the hospital’s strategic objectives.